Choice Deprivation, Choice Overload, and Satisfaction with Choices Across Six Nations. Issue 3 (September 2022) - Reutskaja, Elena; Cheek, Nathan N.; Iyengar, Sheena; Schwartz, Barry
Whether consumers have too little, too much, or the ideal amount of choice can have profound consequences. The present research explores patterns of choice deprivation (having less choice than desired) and choice overload (having more choice than desired) across six choice domains in six countries that together provide home to about half the human population (Brazil, China, India, Japan, Russia, and the United States; combined N = 7, 436). In most domains in most countries, choice deprivation was the norm—only in the United States was choice overload commonly reported. Deprivation was also more strongly related to decreased satisfaction with choices than was overload, suggesting that choice deprivation can be both more common and more consequential than overload. The present research has implications for "inverted U-shape" theories of consumer choice experiences and underlines the need for more diverse samples, including cross-cultural samples, in research on choice deprivation and overload.